2014
DOI: 10.1016/j.virol.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Life of psi: How full-length HIV-1 RNAs become packaged genomes in the viral particles

Abstract: As a member of the retrovirus family, HIV-1 packages its RNA genome into particles and replicates through a DNA intermediate that integrates into the host cellular genome. The multiple genes encoded by HIV-1 are expressed from the same promoter and their expression is regulated by splicing and ribosomal frameshift. The full-length HIV-1 RNA plays a central role in viral replication as it serves as the genome in the progeny virus and is used as the template for Gag and GagPol translation. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 158 publications
4
126
0
Order By: Relevance
“…This observation lends support to the developing hypothesis that retroviral packaging determinants are dynamic in nature and require structural flexibility to allow successful recognition of the packaging substrate RNA that is most likely recognized as a dimer by the Gag proteins [57,49]. Thus, packaging signals may act as ‘structural switches’ that favor either translation or dimerization/packaging of the gRNA, and also help the virus differentiate between spliced and unspliced viral RNAs.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This observation lends support to the developing hypothesis that retroviral packaging determinants are dynamic in nature and require structural flexibility to allow successful recognition of the packaging substrate RNA that is most likely recognized as a dimer by the Gag proteins [57,49]. Thus, packaging signals may act as ‘structural switches’ that favor either translation or dimerization/packaging of the gRNA, and also help the virus differentiate between spliced and unspliced viral RNAs.…”
Section: Discussionsupporting
confidence: 62%
“…The specificity for gRNA during packaging, thus, has been ascribed to high-affinity interactions between the NC domain of Gag and the packaging signal [513]. We have made a similar observation in the case of MPMV, where genetic and structure-prediction analyses have suggested that either ssPurines (Region A) or its partially repeated but base-paired sequence (Region B) plays a crucial role in gRNA packaging, possibly by functioning as a NC binding site [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These RNAs serve as the viral genome (gRNA) and are used as templates for reverse transcription during an early stage of the replication cycle. gRNAs are selected for packaging as dimers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), enabling strand-transfermediated recombination during reverse transcription and facilitating genetic evolution under environmental and chemotherapeutic pressures (23).…”
mentioning
confidence: 99%